2012
DOI: 10.1158/1055-9965.epi-12-0961
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study on Physical Activity and Risk of In Situ Breast Cancer

Abstract: Background: Physical activity has been identified as protective factor for invasive breast cancer risk, whereas comparable studies on in situ carcinoma are rare.Methods: The study included data from 283,827 women of the multinational European Prospective Investigation into C7ancer and Nutrition (EPIC)-cohort study. Detailed information on different types of physical activity conducted during the prior year, such as occupational, recreational, and household activity, as well as on important cofactors, was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 35 publications
3
24
1
Order By: Relevance
“…The multinational European Prospective Investigation into Cancer and Nutrition (EPIC) reported that the association between occupational activity and overall breast cancer risk did not differ by menopausal status [36]. However, when results were stratified by age at diagnosis (age < 50 years versus age ≥ 50 years), inverse risks for invasive [32] and in situ [44] tumors were stronger, but not significant, among women diagnosed at age 50 or older. The EPIC study is also the only other prospective cohort that has evaluated breast cancer risk by body mass index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multinational European Prospective Investigation into Cancer and Nutrition (EPIC) reported that the association between occupational activity and overall breast cancer risk did not differ by menopausal status [36]. However, when results were stratified by age at diagnosis (age < 50 years versus age ≥ 50 years), inverse risks for invasive [32] and in situ [44] tumors were stronger, but not significant, among women diagnosed at age 50 or older. The EPIC study is also the only other prospective cohort that has evaluated breast cancer risk by body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…The EPIC study is also the only other prospective cohort that has evaluated breast cancer risk by body mass index. There were no significant differences in the association between self-reported occupational activity and breast cancer risk among BMI subgroups in the EPIC cohort [44]. …”
Section: Discussionmentioning
confidence: 99%
“…Second, inclusion of in-situ breast cancer could have weakened the preventive effect of physical activity. Four studies that examined risk of in-situ breast cancer in relation to physical activity found no or equivocal association [51,57,72,73]. However, the meta-analysis restricted to studies that included invasive cancer only showed no difference in SRR.…”
Section: Dose-response Analysismentioning
confidence: 99%
“…Hereby, PA acts partly by changing body composition, but effects have also been observed independently of body mass index (BMI) . Moreover, several studies suggest that PA might affect tumor progression rather than tumor initiation …”
mentioning
confidence: 99%
“…3,5,7 Moreover, several studies suggest that PA might affect tumor progression rather than tumor initiation. [10][11][12][13] Some of these primary-preventive effects of PA on breast cancer development might also act after a breast cancer diagnosis, inhibiting progression and improving prognosis. Indeed, evidence is emerging that PA improves survival after breast cancer.…”
mentioning
confidence: 99%